Studies on the low frequency vibration of the suspension system for heavy trucks under different operation conditions. (June 2021) - Jiao, Renqiang; Nguyen, Vanliem
This study proposed a 4 degrees of freedom dynamic model for the two-axle heavy truck to investigate the low frequency vibration characteristics of the suspension system. Unlike the previous research works, the vibration equations of heavy truck model were solved in the frequency domain instead of the traditional time domain based on a calculation method in the complex domain. In order to evaluate the vibration characteristics of the suspension system, parameters of the vehicle velocity, wavelength of the road, load condition, stiffness coefficient, and height of the random road surfaces were then taken into account to clarify their influence on the acceleration frequency characteristics of the suspension system, respectively. The simulation results reveal that the resonant frequency of the suspension system was not affected by the vehicle velocities and road surface profile, while it is greatly influenced by the loading conditions and stiffness of the suspension system. In addition, under different working conditions, the acceleration frequency response characteristics of the vertical and pitch vibration of the heavy truck body and the vertical vibration of the front and rear axles were greatly affected, especially when the vehicle was traveling on the rod of level C at a speed of 30 m s −1 .